2022
DOI: 10.3389/fpsyg.2022.993003
|View full text |Cite
|
Sign up to set email alerts
|

COVID anxiety and its predictors among Slovak adolescents

Abstract: IntroductionThe COVID-19 pandemic and its related restrictions, mainly social distancing, had an impact on the mental health of various groups, including adolescents.MethodsThe main goal of our study was to explore the impact of gender, age, resilience (measured using the Brief Resilience Scale), attachment anxiety, attachment avoidance (both measured using the Experiences in Close Relationships Revised Scale for adolescents), and mental and general health (measured using items of SF-8 Health Survey) on COVID … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Previous studies have identified a host of factors which appear associated with the severity of COVID fear during the pandemic including older age, non-White ethnicity, personality traits, female gender, general level of both physical and mental health. (16,18,34,35,36) Our study builds on this by suggesting that increasing age and being from an at-risk ethnic background also appear to prolong the severity of COVID anxiety, but that other factors which contribute to individuals' COVID-19 risk profile, including having an at-risk health condition and vaccination status, do not appear to affect the trajectory of severe COVID anxiety.…”
Section: Discussionmentioning
confidence: 62%
“…Previous studies have identified a host of factors which appear associated with the severity of COVID fear during the pandemic including older age, non-White ethnicity, personality traits, female gender, general level of both physical and mental health. (16,18,34,35,36) Our study builds on this by suggesting that increasing age and being from an at-risk ethnic background also appear to prolong the severity of COVID anxiety, but that other factors which contribute to individuals' COVID-19 risk profile, including having an at-risk health condition and vaccination status, do not appear to affect the trajectory of severe COVID anxiety.…”
Section: Discussionmentioning
confidence: 62%
“…In the specific case of anxiety, where gender was no longer a significant predictor, it is possible that the levels displayed by the adolescents were directly associated with pandemic COVID-19 (a COVID-19-related anxiety), which would explain why only the number of symptoms in the past few days and the self-reported health status would predict anxiety, and why gender would not. Despite this, some studies have reported higher levels of COVID-19-related anxiety in girls [59,60], and this merit further investigation in the future.…”
Section: Discussionmentioning
confidence: 87%